Pengembangan Modul Pembelajaran Berbasis Blended Learning Mata Pelajaran Rancang Bangun Jaringan - Panyahuti Panyahuti; Kasman Rukun; Waskito Waskito (Pedagogi: Jurnal Ilmu Pendidikan, 2017)
This research is written based on the learning difficulties during industrial internship activities. This research is to produce a learning module for students who implement Prakerin with the Blended Learning model. To know the validity of modules, the effectiveness, and effectiveness of the developed learning modules. The method used is Research and Development (R & D) by using the FOUR D development model that is the definition, design, development, and deployment. The research design used for the trial module is quasi-experiment with a time series model. The module made is valid by the material expert with the average of all eligibility is 80.38%, included in the "Excellent" category. The modular practicality analysis is 81.41%, included in the "Practical" category. Module effectiveness analysis, included in the "Good" category. From both data analysis results done, it can be stated that the module is effective in improving learning outcomes.